Fabrication and Analysis of Carboxylic Acid-Functionalized SWCNT/PDMS-Based Electrodes for ECG Monitoring via IoT - Bani Gandhi; Raghava Srinivasa Nallanthighal (Micro, 2025)
This paper presents the design and fabrication of flexible and gel-less electrodes using carboxylic acid-functionalized single-walled carbon nanotubes (SWCNT-COOHs) and polydimethylsiloxane (PDMS) at thirteen different concentrations. The dispersion was attained by magnetic stirring and sonication using isopropyl alcohol (IPA). Physical characterizations like Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Fourier Transform Infrared Spectroscopy (FTIR) were performed. The electrodes were fabricated using molds. The percolation threshold was achieved at 4 wt%. The ECG results were compared with conventional ECG electrodes and 3.5 wt% displayed the best results. Also, after using the electrodes for 5 days, the ECG signals did not degrade and no skin allergies were observed. The fabricated electrodes are suitable for long-term and continuous ECG monitoring, facilitated with the help of an Internet of Things (IoT) tracking system. The data can then be transmitted to the medical expert and loaded onto the cloud server for analysis.